2020
DOI: 10.1038/s41598-020-71923-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for avascular necrosis in childhood systemic lupus erythematosus in a Taiwanese population

Abstract: Childhood-onset systemic lupus erythematosus (SLE) is associated with greater disease activity, more aggressive course, and high rates of organ damage. The prolonged use of corticosteroids in childhood SLE contributes to increased morbidity, including avascular necrosis (AVN). We conducted this retrospective study using claims data from the Taiwan National Health Insurance Research Database, enrolling 1,472 children with newly-diagnosed SLE between 2005 and 2013. The mean age at the diagnosis of SLE was 15.5 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
9
0
4
Order By: Relevance
“…A recent retrospective study of the Taiwanese population involved 1472 children newly diagnosed with SLE, and 1364 of these patients had DMARDs as a part of their management. 98 Although the patients did not have statistically different usages of DMARD's between the ON and non‐ON groups, the cumulative duration of hydrocychloroquine use was significantly correlated with ON. Association between the use of biologic DMARDs, including Bellimumab 121 and Rituximab, and ON in SLE patients has not been established yet, although Rituximab, an anti‐CD20 antibody, has been suggested as a cause of medication‐related ON of the jaw.…”
Section: Risk Factors For the Development Of On In Patients With Slementioning
confidence: 80%
See 1 more Smart Citation
“…A recent retrospective study of the Taiwanese population involved 1472 children newly diagnosed with SLE, and 1364 of these patients had DMARDs as a part of their management. 98 Although the patients did not have statistically different usages of DMARD's between the ON and non‐ON groups, the cumulative duration of hydrocychloroquine use was significantly correlated with ON. Association between the use of biologic DMARDs, including Bellimumab 121 and Rituximab, and ON in SLE patients has not been established yet, although Rituximab, an anti‐CD20 antibody, has been suggested as a cause of medication‐related ON of the jaw.…”
Section: Risk Factors For the Development Of On In Patients With Slementioning
confidence: 80%
“…Glucocorticoid exposure is a well‐recognized risk factor for ON in SLE patients (Table 1 ). 15 , 16 , 17 , 34 , 35 , 39 , 40 , 41 , 43 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 64 , 65 , 66 , 67 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 In particular, the correlation between ON and the doses of glucocorticoid (GC) therapy has been identified in many studies (Table 1 ) and higher doses of GC therapy have been cited as one of the strongest predictive factors for developing ON. Twenty‐four of 49 studies shown in Table 1 found a significant correlation between the dose of GC therapy and the occurrence of ON in patients with SLE.…”
Section: Risk Factors For the Development Of On In Patients With Slementioning
confidence: 99%
“…The prolong use of corticosteroids in patients with childhood systemic lupus erythematosus (SLE) was shown to increase morbidity and including avascular necrosis (AVN) which is defined as the death of bone due to compromised blood flow. In a retrospective study of 1472 children (mean age 15.5 ± 3.3 years) with newly-diagnosed SLE, 39 patients (2.6%) developed symptomatic AVN during a mean follow-up of 4.6 ± 2.5 years ( Tsai et al, 2020 ) [M]. The multivariate analysis showed that the risk of AVN was higher taking higher dose prednisolone (7.5–30 mg) (HR 7.435, 95% CI 2.882–19.178, P < 0.001) and greater than 30 mg/day (HR 9.366, 95% CI 2.225–39.418, P = 0.002) than in those with a dose ≤ 7.5 mg/day.…”
Section: Systemic Glucocorticoids [Sed-15 906; Seda-33 841; Seda-34 653; Seda-35 719; Seda-36 604; Seda-37 492; Seda-38 425 Seda-42]mentioning
confidence: 99%
“…[ 9 ] Very few clinical studies have compared age-difference SLE characteristics, [ 10 ] but have obtained a similar result, which is that the younger the age of SLE patients, the more severe the disease is. A national-wide healthy insurance registry study analyzed the characteristics of avascular necrosis in childhood SLE [ 11 ] and found 1472 children with newly-diagnosed SLE between 2005 and 2013 in Taiwan. This finding may reflect a significant financial burden if the disease activity is not well-controlled among these SLE children.…”
Section: Introductionmentioning
confidence: 99%